E-mail Security a Pocket Guide - Furnell, Steven (IT Governance Pub., 2010)
This pocket guide will help businesses to address the most important issues. Its comprehensive approach covers both the technical and the managerial aspects of the subject, offering valuable insights for IT professionals, managers and executives, as well as for individual users of e-mail.
Includes bibliographical references. - Print version record
Keywords: Computer security; Electronic mail systems -- Security measures; Computer Security; Sécurité informatique; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; COMPUTERS; Desktop Applications; Email Clients; Electronic mail systems; Security measures